2009
DOI: 10.1111/j.1469-8986.2009.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking emotion: Exposure duration and emotional engagement

Abstract: Effects of exposure duration on emotional reactivity were investigated in two experiments that parametrically varied the duration of exposure to affective pictures from 25-6000 ms in the presence or absence of a visual mask. Evaluative, facial, autonomic, and cortical responses were measured. Results demonstrated that, in the absence of a visual mask (Experiment 1), emotional content modulated evaluative ratings, cortical, autonomic, and facial changes even with very brief exposures, and there was little evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
99
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 23 publications
18
99
2
Order By: Relevance
“…These results are consistent with previous studies that indicate that the LPP modulation presumably reflects the semantic identification of motivationally significant scenes and does not rely on bottom-up perceptual factors, such as complexity, picture size, color, exposure time, or spatial frequencies Codispoti, 2006, 2011;Bradley et al, 2007;Codispoti et al, 2009Codispoti et al, , 2011. Additionally, once affective modulation of the LPP and decision time was first observed, it was maintained despite the repeated presentations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are consistent with previous studies that indicate that the LPP modulation presumably reflects the semantic identification of motivationally significant scenes and does not rely on bottom-up perceptual factors, such as complexity, picture size, color, exposure time, or spatial frequencies Codispoti, 2006, 2011;Bradley et al, 2007;Codispoti et al, 2009Codispoti et al, , 2011. Additionally, once affective modulation of the LPP and decision time was first observed, it was maintained despite the repeated presentations.…”
Section: Discussionsupporting
confidence: 81%
“…Visual processing proceeds in a global-to-local sequence, and limited exposure time acts as a low-pass filter, hindering the perception of local details (De Cesarei and Loftus, 2011). Recent studies have demonstrated that emotional pictures elicit cortical and autonomic changes even under perceptually challenging conditions in which the stimuli are relatively degraded with a very brief exposure duration, but only to the extent that participants could discriminate among emotional picture contents (Codispoti et al, 2009). These findings seem to suggest that scene identification is a conditio sine qua non of affective processing and emotion elicitation (Codispoti et al, 2009;Nummenmaa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, in Experiment 2 we reproduced the paradigm used in Experiment 1, and used ERPs to track picture processing prior to overt response. We focused our analysis on the LPP, which has been suggested to reflect emotional processing of the semantic, rather than perceptual, properties of the stimuli (Bradley, Hamby, Löw, & Lang, 2007;Codispoti, Mazzetti, & Bradley, 2009;Codispoti, De Cesarei & Ferrari, 2012;De Cesarei & Codispoti, 2006;. Moreover, the results of Experiment 1 seem to be in contrast with recent ERP findings on emotional habituation, which show that the emotional modulation of the LPP persists even when the same pictures are repeated 90 times (Codispoti et al, 2007).…”
Section: Methodsmentioning
confidence: 96%
“…The late positive potential (LPP) is a centro-parietal slow wave beginning in the P3 time window, around 300 ms after stimulus presentation, that is more positive for motivationally salient stimuli such as targets or emotional pictures Schupp et al, 2000). This component has been consistently shown to last throughout and beyond picture presentation (Codispoti, Mazzetti, & Bradley, 2009;Hajcak & Olvet, 2008). Furthermore, apart from the intrinsically arousing quality of emotional pictures, the LPP seems to be modulated by cognitive factors, such as working memory load (MacNamara, Ferri, & Hajcak, 2011), target status (Weinberg, Hilgard, Bartholow, & Hajcak, 2012), directed attention (Hajcak, MacNamara, Foti, Ferri, & Keil, 2013), and emotion regulation (Hajcak & Nieuwenhuis, 2006;Paul, Simon, Kniesche, Kathmann, & Endrass, 2013).…”
mentioning
confidence: 99%